Efektivitas Metode Diskusi dalam Meningkatkan Hasil Belajar Bahasa Indonesia Siswa SD: Studi Eksperimen di SD Negeri 86 Palembang - Hasanah, Putri; Akhbar, M. Taheri; Selegi, Susanti Faipri (Jurnal keilmuan dan Kependidikan dasar, 2025)
Indonesian language learning in elementary school plays a crucial role in developing students' language skills and critical thinking. However, preliminary observations at SD Negeri 86 Palembang revealed that teaching is still dominated by the lecture method, resulting in low student motivation and learning outcomes. This study aims to determine the effectiveness of the discussion method on the learning outcomes of fifth-grade students in Indonesian language subjects. The study employed a quantitative approach with a pre-experimental design of the one group pretest-   posttest type. The sample consisted of 25 fifth-grade students selected using the saturated sampling technique. The research instrument was a multiple-choice test of 10 items given before and after the treatment. Data analysis techniques included normality test, homogeneity test, N-Gain, and paired sample t-test. The results showed a significant difference between pretest and posttest scores with a significance value of 0.000 < 0.05. The average pretest score was 58.80, which increased to 84.00 in the posttest. Therefore, the discussion method is proven effective in improving student learning outcomes in Indonesian language subjects for fifth-grade students at SD Negeri 86 Palembang.